Car seat challenge test in the Neonatal Intensive Care Unit - Brás, Ana; Pratinha, Cristina; Oliveira, Susana; Barbieri-Figueiredo, MC; Ramos, Madalena; Guimarães, Hercília (Hygeia Press di Corridori Marinella, 2019)
Background: In Portugal, there is a Guideline of the Directorate General of Health that requires that newborns with hospital discharge should be transported home in a proper and safe restraint system, aligned with AAP policy statements. In the Neonatal Intensive Care Unit (NICU) of Centro Hospitalar Universitário de S. João (Porto, Portugal), the Car Seat Challenge Test has been carried out since 2005, and there is not any study about its safety. Objective: This study aims to report the responses of preterm infants discharged home in 2015 and to develop a standardized procedure for its performance. Methods: This is a descriptive, retrospective, observational, nonexperimental study. Data was collected from the NICU nursing records with a form designed for this purpose. Study variables were: gender, gestational age, birth weight, and comorbidities. Saturation of oxygen in arterial blood (SpO2) and heart rate (HR) values were measured at rest (in the crib), in the car seat chair at time 0, 5, 15, 30, 45 and 60 minutes. Results: During the year 2015, 86 preterm infants were discharged home, and all had values of SpO2 and HR within the reference range for this age group, during the Car Seat Challenge Test. The values decrease slightly from the measurement at 15 minutes for both SpO2 and HR. Infants with and without comorbidities had similar values of SpO2 (97-99.5%) and HR (135- 155 beats per minute [bpm]), with a small decrease at 15 minutes. Infants with comorbidities did not regain saturation values after 30 minutes. Conclusion: The Car Seat Challenge Test has been performed systematically in the NICU since 2005. Data analyzed demonstrated it is safe. A standardized procedure was developed to provide harmonization of criteria.
Keywords: Infant, premature; Child restraint systems; Intensive care units neonatal